2016
DOI: 10.14715/cmb/2016.62.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Safranal prevents rotenone-induced oxidative stress and apoptosis in an in vitro model of Parkinson's disease through regulating Keap1/Nrf2 signaling pathway

Abstract: Safranal, a major constituent of saffron, possesses antioxidant and anti-apoptotic properties showing considerable neuroprotective effects. However, whether safranal shows therapeutic effect on Parkinson's disease (PD) remains unknown. In this study, we aimed to investigate the potential effect of safranal on PD using an in vitro model of PD induced by rotenone. We found that safranal significantly inhibited rotenoneinduced cell death in a dose-dependent manner. Moreover, safranal also markedly suppressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…In a mouse model of asthma, safranal significantly suppressed oxidative stress in the bronchial epithelial cells by inhibiting of inducible nitric oxide synthase and decreasing nitric oxide production [52]. Subsequently, Pan and colleagues showed that safranal ameliorats the ROS production and cell apoptosis mediated by rotenone via regulating nuclear factor E2-related factor 2 (Nrf2)-antioxidant response element signaling pathway, in an in vitro model of Parkinson's disease [53]. In streptozotocininduced diabetic neuropathy model, safranal exhibited potent antioxidant properties by decreasing the levels of MDA in the sciatic nerve tissue [54].…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of asthma, safranal significantly suppressed oxidative stress in the bronchial epithelial cells by inhibiting of inducible nitric oxide synthase and decreasing nitric oxide production [52]. Subsequently, Pan and colleagues showed that safranal ameliorats the ROS production and cell apoptosis mediated by rotenone via regulating nuclear factor E2-related factor 2 (Nrf2)-antioxidant response element signaling pathway, in an in vitro model of Parkinson's disease [53]. In streptozotocininduced diabetic neuropathy model, safranal exhibited potent antioxidant properties by decreasing the levels of MDA in the sciatic nerve tissue [54].…”
Section: Discussionmentioning
confidence: 99%
“…Pan and collaborators (), in an in vitro model of Parkinson's disease, demonstrated that safranal could act as preventive agent against rotenone‐induced oxidative stress and apoptosis by regulating Keap1/Nrf2 signaling pathway. have studied the therapeutic potential of crocetin in a rat model of Parkinson's disease induced by 6‐hydroxydopamine.…”
Section: Potential Therapeutic Applications Of Saffronmentioning
confidence: 99%
“…12,13 The ROS directly contribute to numerous neuronal injuries. [14][15][16][17][18] Therefore, emerging antioxidants have been investigated to remove intracellular ROS and serve as potential therapeutic agents in multiple neurological diseases. [19][20][21] The antioxidant properties of polyphenolic compounds have been widely studied.…”
Section: Introductionmentioning
confidence: 99%